A non-linear hyperelastic finite elemente model of energy return enhacement in sport surfaces and shoes - Baroud, G.; Goerke, U. J.; Guenther, H.; Stefanyshin, D. J.; Miller, J. E.; Nigg, B. M.
The numerical results were experimentally verified using a conventional surface design, and a very good agreement with the force-displacement curves was found. 3-D FE simulations using the new surface also confirmed the results of studies regarding the improvement of energy return (Baroud et al., 1999). A normalized typical energy conservation curve for a sport surface is illustrated in fig 2. The conventional shoe/surface system exhibited a rather limited capacity to deform and consequently, to store and return energy. The energy return for the new structural surface/shoe combination, which was about 14 Joules, was more than 14 times higher than that of the conventional shoe/surface system. This corresponded to about 3% of the average energy expenditure per step during middle distance running (Nigg et al., 1992). The agreement between numerical and experimental results for a sport surface and/or shoe is much better using the proposed hyperelastic than linear elastic material models. Implementing a hyperelastic and, in the future, time-dependent behavior, will contribute to reliable numerical results. The generalized 3-D material model, together with FE modeling presented in this study provides a means to theoretically examine different designs of sport surfaces and/or shoes with respect to their energy storage and return and/or cushioning potential. Construction results need to be verified experimentally since it is not possible to predict how the human body will react to new surfaces and/or shoes. Two aspects which need to be considered further are the frequency of the energy return and the cushioning properties of surfaces and shoes. Since these parameters are coupled with the ability of a surface to deform and return energy, it appears that energy return and cushioning may be coupled into an appropriate concept for constructing sport shoes and surfaces.